2015
DOI: 10.1016/j.mayocp.2014.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Therapy and Cardiovascular Risk: Advances and Controversies

Abstract: Two recent studies raised new concerns regarding cardiovascular (CV) risks with testosterone (T) therapy. This article reviews those studies as well as the extensive literature on T and CV risks. A MEDLINE search was performed for the years 1940 to August 2014 using the following key words: testosterone, androgens, human, male, cardiovascular, stroke, cerebrovascular accident, myocardial infarction, heart attack, death, and mortality. The weight and direction of evidence was evaluated and level of evidence (LO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
171
2
17

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(199 citation statements)
references
References 204 publications
(274 reference statements)
3
171
2
17
Order By: Relevance
“…Of equal importance in this context of higher risk of HF in men is the strong association of andropause with vitamin D deficiency, which can justify this high risk, considering the positive relationship between vitamin D and testosterone levels, as reported in the literature 29. Especially important is the protective effect that testosterone plays on the myocardium, reducing the risk of heart disease and mortality 30. Thus, male seniors in this study are significantly at increased risk of vitamin D deficiency, HF, and higher prevalence of andropause.…”
Section: Discussionmentioning
confidence: 96%
“…Of equal importance in this context of higher risk of HF in men is the strong association of andropause with vitamin D deficiency, which can justify this high risk, considering the positive relationship between vitamin D and testosterone levels, as reported in the literature 29. Especially important is the protective effect that testosterone plays on the myocardium, reducing the risk of heart disease and mortality 30. Thus, male seniors in this study are significantly at increased risk of vitamin D deficiency, HF, and higher prevalence of andropause.…”
Section: Discussionmentioning
confidence: 96%
“…Even if there is some supportive exprimental data (19), the causality between testosterone levels and CVD remains elusive. During the past 4 years, several independent studies, published in prestigious journals, have shown men treated with testosterone to have increased amount of cardiovascular symptoms (2, 3, 4, 5, 6), which has created heated debate around the testosterone vs CVD issue (20,21).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…11 The severity of CAD has also been investigated as a function of serum T concentrations. Four studies have noted an inverse relationship between serum T levels and CAD severity, 6 with lower levels of serum T associated with more severe CAD and higher serum T levels associated with reduced severity. 11 However, these results should be interpreted with caution due to the relatively small sample size included in each study.…”
Section: Testosterone Deficiency and Coronary Artery Diseasementioning
confidence: 99%
“…Many studies have indicated that low serum T concentrations are associated with increased CV risk and mortality and that TRT may have clinically relevant CV benefits. 6 Two recent observational studies reported increased CV risks in men who received testosterone prescriptions. 17,18 Although they gained a significant amount of media attention, neither study provided credible evidence of increased CV risk.…”
Section: Impact Of Testosterone Replacement Therapy Overall Mortalitymentioning
confidence: 99%
See 1 more Smart Citation